2019
DOI: 10.3390/ijms20112640
|View full text |Cite
|
Sign up to set email alerts
|

Helium-Induced Changes in Circulating Caveolin in Mice Suggest a Novel Mechanism of Cardiac Protection

Abstract: The noble gas helium (He) induces cardioprotection in vivo through unknown molecular mechanisms. He can interact with and modify cellular membranes. Caveolae are cholesterol and sphingolipid-enriched invaginations of the plasma-membrane-containing caveolin (Cav) proteins that are critical in protection of the heart. Mice (C57BL/6J) inhaled either He gas or adjusted room air. Functional measurements were performed in the isolated Langendorff perfused heart at 24 h post He inhalation. Electron paramagnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 56 publications
(77 reference statements)
1
24
1
Order By: Relevance
“…Thirty minutes or 24 h after the experimental protocol, hearts were excised and blood was withdrawn from animals. In strong contrast to our initial hypothesis, the mice heart showed a significant downregulation of caveolin-1 and caveolin-3 after 24 h [58]. Subsequent sub-fractionation of the whole heart showed that specifically the membrane fractions, but not the cytosolic fractions, had decreased levels of caveolin-1 and caveolin-3.…”
Section: A Novel Target For Helium Conditioning: Membrane Proteins “Ccontrasting
confidence: 94%
See 3 more Smart Citations
“…Thirty minutes or 24 h after the experimental protocol, hearts were excised and blood was withdrawn from animals. In strong contrast to our initial hypothesis, the mice heart showed a significant downregulation of caveolin-1 and caveolin-3 after 24 h [58]. Subsequent sub-fractionation of the whole heart showed that specifically the membrane fractions, but not the cytosolic fractions, had decreased levels of caveolin-1 and caveolin-3.…”
Section: A Novel Target For Helium Conditioning: Membrane Proteins “Ccontrasting
confidence: 94%
“…The addition of helium conditioned serum to muscle cells in cell culture or naïve ventricular tissue increased mitochondrial metabolism without increasing ROS generation. Measurements of primary and lipid metabolites showed potential changes in ceramide in helium-conditioned serum [58]. Data from this mice study is in line with our previous findings in human endothelial cells investigating the direct effects of helium in vitro [59].…”
Section: A Novel Target For Helium Conditioning: Membrane Proteins “Csupporting
confidence: 88%
See 2 more Smart Citations
“…Helium induced changes in circulating caveolin in mice suggest a novel mechanism of cardiac protection [27]. In a rat model of resuscitation, one study examined the effects of helium pre-and postconditioning on the brain and heart [28].…”
Section: Protection Of Nerves and The Heartmentioning
confidence: 99%